Reputação e gestão de crise de integridade: a Odebrecht retratada na mídia impressa no contexto da Lava Jato - Martins, Amanda Frick (2023)
In the corporate world, it is well known that integrity crises have the ability to quickly transform the reputation of any organization. Under conditions of profound societal pressure for ethical and responsible stances, companies find positive reputation to be an important competitive asset. The urgency in restoring the reputation of organizations involved in integrity crises, along with the importance of rebuilding trust among stakeholders, forms the problematic of the theoretical discussions presented in this thesis. Thus, the guiding problem of the research inquiries into how newspapers Estadão, Folha de São Paulo, and Valor Econômico portrayed the attempts to rebuild Odebrecht's reputation in the context of the Lava Jato operation. The thesis is theoretically organized around the concepts of reputation by Fombrun (1996), Fombrun and Van Riel (2004), Davies et al. (2003), Bueno (2009, 2018), and Barros Filho and Peres Neto (2019). For the concepts of ethics and integrity crises, we employ Srour (2005), Bueno (2009), Ashley (2005), Han (2017), Forni (2019), and Paraventi (2016, 2020). The mediatized society, public opinion, and media interests are conceptualized by Sodré (2002), Braga (2007), Lippmann (2008), Charaudeau (2016), and Rudiger (2011). The methodology used was qualitative and interpretative. The methods employed included bibliographic and documentary research (MOREIRA, 2012), covert and non-participatory observation (JOHNSON, 2010), mapping of the publics involved in the integrity crisis based on Locatelli (2011), and content analysis by Bardin (1979) adapted by Fossá (2003). As a result, we arrived at two final categories of content analysis, named: "the media portrays the search for ethics in the new integrity" and "the crisis content in the media dictates the new reputation." These categories reinforce the reputation and integrity theories explained in the thesis and indicate the concept of media reputation that portrays Odebrecht based on its actions in pursuit of integrity and the crisis environment performed through the communication advisory of the Federal Public Ministry together with the editorial offices of the analyzed newspapers.